Effects of Green Tea (−)-Epigallocatechin-3-Gallate (EGCG) on Cardiac Function - A Review of the Therapeutic Mechanism and Potentials - Li, Yuejin; Karim, Md. R.; Wang, Buheng; Peng, Jiangnan (Mini Reviews in Medicinal Chemistry, 2022)
Heart disease, the leading cause of death worldwide, refers to various illnesses that affect heart structure and function. Specific abnormalities affecting cardiac muscle contractility and remodeling and common factors including oxidative stress, inflammation, and apoptosis underlie the pathogenesis of heart diseases. Epidemiology studies have associated green tea consumption with lower morbidity and mortality from cardiovascular diseases, including heart and blood vessel dysfunction. Among the various compounds found in green tea, catechins are believed to play a significant role in producing benefits to cardiovascular health. Comprehensive literature reviews have been published to summarize the tea catechins' antioxidative, anti-inflammatory, and anti-apoptosis effects in various diseases, such as cardiovascular diseases, cancers, and metabolic diseases. However, recent studies on tea catechins, especially the most abundant (−)-Epigallocatechin-3-Gallate (EGCG), revealed their capabilities in regulating cardiac muscle contraction by directly altering myofilament Ca2+ sensitivity on force development and Ca2+ ion handling in cardiomyocytes under both physiological and pathological conditions. In vitro and in vivo data also demonstrated that green tea extract or EGCG protected or rescued cardiac function, independent of their well-known effects against oxidative stress and inflammation. This mini-review will focus on the specific effects of tea catechins on heart muscle contractility at the molecular and cellular level, revisit their effects on oxidative stress and inflammation in various heart diseases, and discuss EGCG's potential as one of the lead compounds for new drug discovery for heart diseases.
Keywords: ischemic heart diseases